Critical care service delivery across healthcare systems in low-income and low-middle-income countries: protocol for a systematic review - Srinivas Murthy; Teri Reynolds; Richard Lowsby; Neill KJ Adhikari; Andrew George Lim; Lia Ilona Losonczy; Michael S Jaung; Sojung Yi; Sean Kivlehan; Enrico Dippenaar; Marc Li Chuan L C Yang; P Andrew Stephens; et al. (BMJ Open)
Introduction Critical care in low-income and low-middle income countries (LLMICs) is an underdeveloped component of the healthcare system. Given the increasing growth in demand for critical care services in LLMICs, understanding the current capacity to provide critical care is imperative to inform policy on service expansion. Thus, our aim is to describe the provision of critical care in LLMICs with respect to patients, providers, location of care and services and interventions delivered.Methods and analysis We will search PubMed/MEDLINE, Web of Science and EMBASE for full-text original research articles available in English describing critical care services that specify the location of service delivery and describe patients and interventions. We will restrict our review to populations from LLMICs (using 2016 World Bank classifications) and published from 1 January 2008 to 1 January 2020. Two-reviewer agreement will be required for both title/abstract and full text review stages, and rate of agreement will be calculated for each stage. We will extract data regarding the location of critical care service delivery, the training of the healthcare professionals providing services, and the illnesses treated according to classification by the WHO Universal Health Coverage Compendium.Ethics and dissemination Reviewed and exempted by the Stanford University Office for Human Subjects Research and IRB on 20 May 2020. The results of this review will be disseminated through scholarly publication and presentation at regional and international conferences. This review is designed to inform broader WHO, International Federation for Emergency Medicine and partner efforts to strengthen critical care globally.PROSPERO registration number CRD42019146802.